Impact of tropospheric ozone on terrestrial biodiversity: A literature analysis to identify ozone sensitive taxa - Elke Bergmann; Jürgen Bender; Hans-Joachim Weigel (Journal of Applied Botany and Food Quality, 2017)
Tropospheric ozone has long been known as highly phytotoxic. However, currently hardly anything is known whether this air pollutant can also pose a threat to the overall biodiversity in terrestrial ecosystems. Identifying the relative ozone sensitivities of relevant taxa or species can be a first step in an assessment if biodiversity is at risk from ozone. A literature survey was conducted describing experimental and observational results of exposure of organisms and particularly plant species to ozone at environmentally relevant concentrations. For plants ozone effects considered were vegetative growth (e.g. biomass of shoots, foliage, single leaves, stems, and roots), reproduction (number and biomass of seeds and flowers), species development, and symptoms of visible foliar injury. A total of 474 literature references were evaluated which described such effects. For crop plants 54 species with 350 varieties could be considered, while (semi)natural vegetation was represented by 465 vascular plant species comprising 298 herbaceous and 165 woody plant species. Overall, these ozone studies cover only a small fraction of the entire global flora. About two third of woody and about one half of native herbaceous plant species investigated so far have been described as ozone sensitive in at least one study. Ozone sensitivity is slightly higher with respect to visible leaf injury as compared to growth effects, and herbs and deciduous tree species are more responsive than grasses and coniferous trees. Observational results from field surveys conducted along ozone gradients to assess ecosystem effects of ozone in North America and Europe revealed visible macroscopic leaf injuries for 258 herbaceous species. However, these findings often have not been verified under experimental ozone exposure. Albeit the numbers of ozone studies related to a particular plant family varied considerably, high proportions of ozone sensitive species were found e.g. for the families Myrtaceae, Salicaceae and Onograceae, while low proportions of ozone sensitive species were found e.g. for the families Brassicaceae, Boraginaceae and Plantaginaceae. Intra-specific variations of ozone sensitivity of vascular plants were primarily detected in crop species (e.g. wheat, soybean, snap bean, clover, rice), most often derived from screening studies of cultivars for their relative ozone sensitivity/tolerance to ozone. In some cases intra-specific variation of ozone sensitivity is also true for different populations of woody and herbaceous plant species, which often resulted from temporal or spatial differentiation of the relative ozone susceptibility. Therefore, there is some evidence that ozone pollution in the past has already affected plant selection and modified the genetic pool of ozone sensitive genotypes. Information on direct ozone effects on species other than vascular plants (e.g. ferns, mosses, fungi, algae, vertebrates) is very poor or irrelevant, i.e. ozone sensitivities for these taxa could not be described. This is also true for organisms like microbes, arthropods or insects which have not been tested so far for their responses to direct ambient ozone exposure. However, these organisms may be indirectly impaired by ozone via loss of vitality of the plant system to which they are associated.